The Representation of the commons in climate change coverage by Business Mirror discourse analysis - Cristobal, Ruby Roan 1957- (College of Mass Communication, University of the Philippines Diliman, 2018)
"This dissertation examined how Business Mirror represented the commons in the coverage of climate change, using the theoretical models of the tragedy of the commons by Garrett Hardin (1968) and the management of common-pool resources through collective action by Elinor Ostrom (1990), to understand media discourse on climate change. The research also employed discourse analysis to elucidate on the linked relationships of climate change news, journalistic norms, and the climate change regime. The results showed that the atmosphere, as the commons in climate change, was represented in the coverage as a managed limited resource that is almost reaching its threshold. The users of the atmosphere as a climate commons were portrayed as cooperative towards pursuing a collective action to address climate change, reflecting Ostrom's principles in managing common-pool resources. Hardin's description of open-access resources and their users were gleaned from the stories that depicted the arguments of civil society regarding historic emissions of greenhouse gases and climate financing by developed countries. The discursive representations also reflected the personal beliefs and advocacies of the journalists on the value of taking care of the environment, and the importance of developing mitigation and adaptation policies by local, national, and international institutions. The reporters usually assigned to cover climate change were also covering other beats and some were not working full time as journalists. This situation most likely accounted for the dependence on the news wires as sources of climate change stories. The coverage was also event-centered, with most of the articles coming from foreign news wire service, and often using authority-order and dramatization. It dominantly reflected the discourse of developed countries and the climate change regime. The discursive representation in the coverage of climate change by Business Mirror during the period covered by the study was found to be devoid of the theoretical value of the commons perspective, as the voice of those who represent the climate change regime was privileged and often without a deeper probe into their arguments. The coverage revealed the following dominant discourses on climate change: 1) economic discourse presented through the contending arguments about climate change financing; 2) political discourse demonstrated by the power relations among the stakeholders to climate change action; 3) discourse of government shown by the commitment of countries toward mitigation and adaptation measures; 4) discourse of equity and justice reflected in the demand by civil society of the developing countries for developed countries and historical emitters to aim for deeper cuts in emission, for transparent and binding monitoring rules, and clearer reporting of climate financing; 5) discourse of disaster which highlighted the vulnerability of small island states, other ecosystems, biodiversity, culture and the weather and climate systems to the catastrophic impacts of climate change; and 5) discourse of victims portrayed in the arguments of civil society and other groups that emissions should be accounted based on historical rather than current greenhouse gas loading by developed countries."